EXPERIMENTAL INVESTIGATION ON THE USE OF NATIVE BIOMASS AS BIOSORBENTS FOR METAL POLLUTANT REMOVAL - Litto, R.; Mmbaga, J. P.; Mushi, T. P. (Tanzania Journal of Engineering and Technology, 2018)
Abstract